58 First-phase ejection fraction predicts repsonse to cardiac resynchronization therapy and adverse outcomes. (17th July 2020) - Gu, Haotian; Sidhu, Baldeep; Fang, Lingyun; Webb, Jessica; Jackson, Tom; Claridge, Simon; Razavi, Reza; Chowienczyk, Phil; Rinaldi, Aldo
Abstract : Background: Cardiac Resynchronization Therapy (CRT) is an important therapeutic treatment for chronic heart failure. However, even in carefully selected cases up to 40% of patient fail to respond. First-phase ejection fraction (EF1), the ejection fraction up to the time of maximal ventricular contraction, is a novel and more sensitive echocardiographic measure of early systolic function. We examined the value of EF1, to predict response to CRT and clinical outcomes after CRT. Methods: Echocardiography was performed in 197 patients (table 1) who underwent CRT between 2009 and 2018 and were followed to determine clinical outcomes. LV volumes were measured by 2D Simpson's method from apical views at end-diastole, time of peak aortic valve flow and end-systole to give end-diastolic volume (EDV), volume at TPAVF (V1) and ESV. 3D echocardiography was performed in a sub-sample of patients (n=73) allowing automated determination of EF1. EF1 was calculated as the percentage change between EDV and V1: EF 1= (EDV – V1) / EDV x 100 %. Results: Volumetric response rate (reduction in end-systolic volume ≥ 15%) was 92.3% vs. 12.1%, for those with EF1 in the highest vs. lowest tertiles (p<0.001). A cut-off value of 11.9% for EF1 had > 85% sensitivity and specificity for prediction of response to CRT; on multivariate binary logistic regression analysis incorporating previously defined predictors (table 2) EF1 was the strongest predictor of response (odds ratio: 1.563, 95% confidence interval: 1.371-1.782, per 1% change in EF1, p<0.001). EF1 was also the strongest predictor of a clinical composite score (odds ratio: 1.115, 95% confidence interval: 1.044-1.191, p=0.001). The c-statistic index for a logistic model (including age, gender, presence of AF, ischaemic aetiology, SF, ApRock, presence of LBBB and QRS duration) increased significantly by adding EF1 (from 0.720 to 0.922: change in the c-statistic 0.202, p<0.01). Improvement in EF1 at 6 months (figure 1) after CRT implantation (6.5±5.8% vs 1.8±4.3% in responders vs. non-responders, p<0.001) was the best predictor of heart failure re-hospitalization and death after median follow-up of 29.2 months (HR: 0.819, 95%CI:0.765-0.876, p<0.001) (figure 2). Conclusion: EF1, a simple measure of early systolic function, is a promising predictor of response to CRT and may be useful in selecting patients for CRT and as a target for optimising CRT and other measures to improve outcomes in patients with HFrEF. Conflict of Interest: None